Bridging Ideologies in Translation: An Ideological Critical Stylistic Analysis of Yemeni Conflict Discourse - Manal Abdulkareem Mohammed; Belqes Saif Abdulelah Al-Sowaidi (Taez University, 2023)
This study investigates how reframing strategies and linguistic aspects are employed to legitimize and normalize ideologically loaded narratives introduced by the Yemeni internationally recognized government (YIRG), with a particular focus on the impact of dominant ideologies and the translator's political and social affiliations on the target texts. Combining frameworks from different fields, the study draws upon Baker's (2006) narrative theory and Jeffrie's (2010) model of critical stylistics to provide a comprehensive understanding of the translation process and its management during conflict. Analyzing English-language materials translated into Arabic, the study utilizes source English materials, including news, reports, and opinions, from Western media outlets. The corresponding Arabic translations are drawn from media belonging to the YIRG. The study concludes that the YIRG's dominant ideology significantly constrains the political translation process during the conflict. This ideology is reflected in the reframing of narratives to align with the adopted ideology, encompassing the repositioning and labeling of participants according to the prevailing ideology. Moreover, textual choices, grammatical and semantic, influence the translator's representation of events, word choice, and pragmatic references to the opposing party through deictic expressions.